(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
This research provides a brief overview of GAI and AI applications in major parts of the world. After this, it will try to demystify GAI and AI literacy. Finally, it will discuss how the American University of Nigeria (AUN) and Africa will benefit from these fantastic tools to improve and perhaps lead HE. AUN has a great opportunity to become one of the world's leading universities in this area.